OC-065 Functional Cortical Swallowing Activity And Neurotransmitters Concentrations Are Altered Following Neurostimulation Of Pharyngeal Motor Cortex: An Fmri And Resonance Spectroscopy (mrs) Study. (9th June 2014) - Michou, E; Mistry, S; Vidyasagar, R; Downey, D; Williams, S; Hamdy, S
Abstract : Introduction: Combined pharyngeal electrical and transcranial-magnetic-stimulation or paired associative stimulation (PAS) is shown to induce beneficial neurophysiological and behavioural effects on swallowing in health and dysphagic stroke patients (Michou et al ., Gastroenterology 2012). Here, we investigate brain changes during swallowing following application of PAS, using fMRI and MR spectroscopy to measure neural activity and GABA concentrations in the motor cortices. Methods: Healthy adults (n = 11, 38 ± 9 yoa) were randomised to receive real and sham PAS on 2 separate visits. Event-related fMRI was performed to assess changes in brain activations in response to water and saliva swallowing and during rest. Data were analysed (SPM8), applying p < 0.001 uncorrected thresholds with contrasts of 'water swallowing-rest' and 'saliva swallowing-rest'. MRS data were acquired before and after the fMRI on both visits and GABA concentrations were measured (AMARES, jMRUI). Results: Following real PAS, group analyses of 'water swallowing-rest' and 'saliva swallowing-rest' showed increased activation in motor and premotor areas bilaterally. Moreover, real PAS increased activations prominently in premotor areas contralateral to PAS (Figure 1 group mean brain activations following real PAS). Following real PAS, GABA concentrations in motor cortex decreased significantly both ipsilateral (P = 0.008) and contralateral (P = 0.013) to PAS. Conclusion: Targeted neurostimulation applied to the human pharyngeal motor cortex induces local and remote changes in both primary and non-primary areas for water and saliva tasks. Moreover, stimulation leads to reduction of the inhibitory neurotransmitter GABA, when associated with swallowing. These findings allow us to understand the mechanisms underlying the beneficial effects of neurostimulation in modulating the brain swallowing network. Disclosure of Interest: None Declared.